2018
DOI: 10.24200/sci.2018.20701
|View full text |Cite
|
Sign up to set email alerts
|

Determination of limit-states for near-fault seismic fragility assessment of concrete gravity dams

Abstract: Fragility curve, based on the Performance-Based Earthquake Engineering (PBEE), is a fundamental tool for assessing the probabilistic seismic performance of concrete gravity dams. Determination of the dam Limit-States (LSs) is necessary for estimation of fragility curve. In this research, four LSs in seismic performance of massive structure have been utilized for Pine Flat dam. To address this, the Incremental Dynamic Analysis (IDA) method has been applied to the integrated dam-reservoir nite-element model. Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The damages of the dam body usually occur in the base (heel and toe), in the crown and in the points where the slopes change. The cracks can propagate along the whole upstream and downstream face as shown in literature [45][46][47].…”
Section: Results Of the Damage Estimationmentioning
confidence: 99%
“…The damages of the dam body usually occur in the base (heel and toe), in the crown and in the points where the slopes change. The cracks can propagate along the whole upstream and downstream face as shown in literature [45][46][47].…”
Section: Results Of the Damage Estimationmentioning
confidence: 99%
“…Another study tested pore water pressure in an earth dam to assess the mechanical stability using a 2D random FE method with Monte Carlo simulation [131]. Sotoudeh et al [132] evaluated the seismic behavior, demand, and capacity of concrete dams using incremental dynamic analysis with an FE model. The results showed that the exceeded probability of the limit-states curves measured at different intensities is a useful tool for probabilistic framework studies.…”
Section: D Dam Modelingmentioning
confidence: 99%
“…Fattahi and Gholizadeh assessed the seismic performance of optimally designed steel moment frames in three phases, including optimization to meet the performance requirements, derivation of the fragility curves, and generation of the fragility curves for different damage levels [23]. Sotoudeh et al [24] developed four limit states to be used in seismic performance evaluation of massive concrete dams using incremental dynamic analysis. It was applied to an integrated dam-reservoir finite-element model and was used to assess the probabilistic performance of the Pine Flat dam.…”
Section: Introductionmentioning
confidence: 99%